The Effect of Reflective-Impulsive Conceptual Thinking Style Models and Learning Models on Learning Outcomes of Complex Analysis by Controlling Students' Initial Knowledge - I Made Sugiarta (Universitas Pendidikan Ganesha, 2023)
Concept understanding of complex analysis is very necessary for students of the Mathematics Education Department. Considering the concepts contained in Mathematics course are needed by students, especially in developing reasoning power in related material and solving problems. This study aims to analyze interactions between the reflective-impulsive conceptual thinking style model and the learning model on learning outcomes of complex analysis by controlling initial knowledge. This research is a quasi-experimental research involving 92 students of the Department of Mathematics Education as a sample. The sampling technique to determine each treatment group is simple random sampling. This study uses a 2x2 factorial design. Data analysis was performed using analysis of covariance (ANCOVA). The results showed that the learning outcomes of complex analysis of groups of students who followed the generative learning model were higher than those who followed conventional learning models. The learning outcomes of complex analysis of groups of students who had a reflective thinking style were higher than those who had an impulsive style. There was an influence of interaction between the learning model and conceptual thinking style on student complex analysis learning outcomes. Generative model learning has implications for increasing mastery of concepts, which are closely related to initial abilities.